Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1126/sciadv.abf7114
|View full text |Cite
|
Sign up to set email alerts
|

NOX4 links metabolic regulation in pancreatic cancer to endoplasmic reticulum redox vulnerability and dependence on PRDX4

Abstract: There is an urgent need to identify vulnerabilities in pancreatic ductal adenocarcinoma (PDAC). PDAC cells acquire metabolic changes that augment NADPH production and cytosolic redox homeostasis. Here, we show that high NADPH levels drive activity of NADPH oxidase 4 (NOX4) expressed in the endoplasmic reticulum (ER) membrane. NOX4 produces H2O2 metabolized by peroxiredoxin 4 (PRDX4) in the ER lumen. Using functional genomics and subsequent in vitro and in vivo validations, we find that PDAC cell lines with hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…To date, several of their physiological functions include, but are not limited to, cell signalling, phagocyte function in innate immunity (NOX2), host defence (NOXA, RBOHs and NOX2), thyroid hormone synthesis (DUOXs), tolerance to stress and plant cell signaling (RBOHs), cell differentiation, mitogenic functions and cell proliferation and differentiation (NOX4, NOXB) [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. Mutations affecting function of the human NOXs cause severe diseases such as chronic granulomatous disease (NOX2), and NOX dysregulation has been attributed to cardiovascular, neurological disorders (NOX2, NOX4), and pulmonary diseases and cancers (NOX1 and NOX4) [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several of their physiological functions include, but are not limited to, cell signalling, phagocyte function in innate immunity (NOX2), host defence (NOXA, RBOHs and NOX2), thyroid hormone synthesis (DUOXs), tolerance to stress and plant cell signaling (RBOHs), cell differentiation, mitogenic functions and cell proliferation and differentiation (NOX4, NOXB) [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. Mutations affecting function of the human NOXs cause severe diseases such as chronic granulomatous disease (NOX2), and NOX dysregulation has been attributed to cardiovascular, neurological disorders (NOX2, NOX4), and pulmonary diseases and cancers (NOX1 and NOX4) [ [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%
“…The tumors in transgenic groups also had lower oxidative stress and higher macrophage infiltration. Furthermore, Prx4 has been suggested to promote progression of prostate cancer, pancreatic cancer, hepatocellular carcinoma and colorectal cancer [ 17 , 40 , 41 , 42 ]. Lastly, loss of Prx4 providing resistance to colitis fits the general trend observed when antioxidant enzymes are depleted in colitis models: loss of Prx1, Prx2, and Prx6 and the combined loss of GPx1 and catalase all improved colitis in mouse and rat models [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the upregulated PRDX4 might play an oncogene function in provoking proliferation, metastasis, and invasion, leading to a poor prognosis of HNSCC patients, which is confirmed in OSCC ( 14 ). The silencing of PRDX4 is related to the generation of ROS in the endoplasmic reticulum, which diffuses to the nucleus and induces DNA damage ( 30 ). In addition, PRDX4 can reduce the expression of adhesion molecules ( 31 ), thereby increasing the possibility of metastasis and invasion.…”
Section: Discussionmentioning
confidence: 99%